Classroom Management Skills and Pupils’ Learning Outcomes in Elementary Araling Panlipunan, Philippines: A Correlational Study in the Philippines - Analyn G. Fernandez; Nhelbourne K. Mohammad (Journal of Educational Technology Innovation and Applications, 2026)
Classroom management is essential to effective teaching, yet limited evidence exists on how its specific dimensions relate to pupil achievement in elementary Araling Panlipunan (AP). This study examined the relationship between teachers’ classroom management skills and pupils’ learning outcomes in public elementary schools in Zamboanga del Norte, Philippines. Using a quantitative descriptive-correlational design, data were gathered from teachers and pupils through a validated questionnaire and official academic records. Data were analyzed using weighted mean, Pearson correlation, and multiple regression. Findings showed that teachers demonstrated high levels of classroom management skills, particularly in instructional management and classroom organization, while pupils achieved very satisfactory learning outcomes in AP. Results also revealed a significant positive relationship between classroom management and pupil achievement. Among the dimensions examined, instructional management emerged as the strongest predictor of learning outcomes, followed by classroom organization, discipline, and learner engagement. The findings highlight the critical role of effective instructional management in improving pupil achievement and support the development of evidence-based intervention programs.